1998
DOI: 10.1016/s1078-5884(98)80205-0
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal variation in the incidence of ruptured abdominal aortic aneurysms

Abstract: There is a seasonal variation in the incidence of recorded deaths from abdominal aortic aneurysm in England and Wales, with a peak of deaths in the cold winter months. The underlying cause is unknown, but hypertension and tobacco smoking are predisposing factors to aortic aneurysm rupture. Exposure to tobacco smoke is known to be greater indoors in cold weather and there is a winter peak of blood pressure in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 17 publications
0
44
1
2
Order By: Relevance
“…month of January, much akin to the winter peak seen for other cardiovascular events. 3,11,17,18 This finding suggests a common link regarding the pathophysiology/triggering of these events. Subgroup analysis suggested that this monthly/seasonal pattern was more evident in patients who were young (aged Ͻ70 years), in women, and in normotensive and nondiabetic individuals but not among older patients, men, and hypertensive or diabetic patients, who are otherwise at a high-risk for most cardiovascular events.…”
Section: Discussionmentioning
confidence: 69%
“…month of January, much akin to the winter peak seen for other cardiovascular events. 3,11,17,18 This finding suggests a common link regarding the pathophysiology/triggering of these events. Subgroup analysis suggested that this monthly/seasonal pattern was more evident in patients who were young (aged Ͻ70 years), in women, and in normotensive and nondiabetic individuals but not among older patients, men, and hypertensive or diabetic patients, who are otherwise at a high-risk for most cardiovascular events.…”
Section: Discussionmentioning
confidence: 69%
“…During peripheral vasoconstriction, systolic pressure increases more than diastolic which increases the pulse wave, leading to the rupture of abdominal aortica aneurysm. However, there are data (1,3) showing the outbreak of rupture of abdominal aortic aneurysm during spring and autumn. Therefore, it cannot be proven that rupture of abdominal aortic aneurysm is connected with low temperature and season of the year.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of climatic factors on the rupture of abdominal aorta is geographically dependent. Studies carried out in Canada (1) and United Kingdom (2) have shown a higher incidence of rupture during autumn and spring, while studies in England, Wales (3) and Western Australia (4) during winter season. In the southwestern Greece, 78% of all ruptures occur in April and October (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the research performed in the fields of pathology and molecular biology, investigations have been conducted focusing on other factors that are potentially related to aneurysm ruptures. One interesting possible factor in this regard is the influence of weather conditions, primarily the influence of the atmospheric pressure on the potential for an aneurysm rupture [5][6][7]. Despite the important role of the AAA's diameter itself, an aneurysm rupture may also occur either in cases of small aneurysms or in areas that do not necessarily have the largest diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting results are found in the available literature concerning the influence of atmospheric pressure on aneurysm rupture [5][6][7][9][10][11][12][13]. The relatively small sizes of the evaluated populations and the lack of an analysis of the aneurysms' sizes did not allow determination of the influence of the atmospheric pressure on the AAA ruptures.…”
Section: Introductionmentioning
confidence: 99%